Application of polish experience in the implementation of the flood directive in Georgia – hydrological calculations - Diana Egiazarova; Marina Kordzakhia; Andrzej Wałęga; Edyta Drożdżal; Marta Milczarek; Anna Radecka (Acta Scientiarum Polonorum. Formatio Circumiectus)
This paper present an example of the implementation of hydrological calculation methods for delineation of flood risk zones in the conditions prevailing in Georgia. The results, described in the present paper, were obtained in the project “Study of hydraulic modelling against floods – 2nd stage – support to the competence and readiness of Georgian institutions” which was organized and implemented by Polish Center for International Aid (PCPM), and co-funded by the Ministry of Foreign Affairs of the Republic of Poland. The results related to the catchments of the Lopota, the Intsoba, the Chelti, the Avaniskhevi, the Shromiskhevi in Kakheti and the Aragvi. All the catchments named above are hydrologically ungauged, therefore, a rainfall-runoff hydrological model was required for generating hypothetical hydrographs. Based on the peak daily total rainfall for the multi-annual period 1966–2014, quantiles of rainfall with a specified exceedance probability were calculated. A rainfall hyetogram was found using the beta distribution function. Effective rainfall was calculated by the SCS-CN method. Details of the land profile, cover and soil conditions were obtained from the numerical land model as well as maps, generated as part of the project named above. The effective rainfall was transformed into runoff using a simple SCSUH model, based on the synthetic unit hydrograph. Studies indicated that total daily uniform rainfalls were random and could be described using the Fisher-Tippett distribution type III min. The results obtained by modeling were boundary conditions in the hydraulic model of transformation of the flood wave in rivers.